Babesiosis Occurrence Among United States Medicare Beneficiaries, Ages 65 and Older, During 2006–2017: Overall and by State and County of Residence. (15th December 2020) - Menis, Mikhail; Whitaker, Barbee I; Wernecke, Michael; Jiao, Yixin; Eder, Anne; Kumar, Sanjai; Xu, Wenjie; Liao, Jiemin; Wei, Yuqin; MaCurdy, Thomas E; Kelman, Jeffrey A; Anderson, Steven A; et al.
Abstract: Background: Human babesiosis is a mild-to-severe parasitic infection that poses health concerns especially in older and other at-risk populations. The study objective was to assess babesiosis occurrence among US Medicare beneficiaries, ages 65 and older, during 2006–2017. Methods: Our retrospective claims-based study used Medicare databases. Babesiosis cases were identified using recorded diagnosis codes. The study estimated rates (per 100 000 beneficiary-years) overall, by year, diagnosis month, demographics, and state and county of residence. Results: Nationwide, 19 469 beneficiaries had babesiosis recorded, at a rate of 6 per 100 000 person-years, ranging from 4 in 2006 to 9 in 2017 ( P  < .05). The highest babesiosis rates by state were in the following: Massachusetts (62), Rhode Island (61), Connecticut (51), New York (30), and New Jersey (19). The highest rates by county were in the following: Nantucket, Massachusetts (1089); Dukes, Massachusetts (236); Barnstable, Massachusetts (213); and Dutchess, New York (205). Increasing rates, from 2006 through 2017 ( P  < .05), were identified in multiple states, including states previously considered nonendemic. New Hampshire, Maine, Vermont, Pennsylvania, and Delaware saw rates increase by several times. Conclusions: Our 12-year study shows substantially increasing babesiosis diagnosis trends, with highest rates in well established endemic states. It also suggests expansion of babesiosis infections in other states and highlights the utility of real-world evidence.